The dynamics of social capital in influencing use of soil management options in the Chinyanja Triangle of southern Africa - Njuki, Jemimah; Mapila, MT; Zingore, Shamie; Delve, Robert J. (2008)
Social capital has become a critical issue in agricultural development as it plays an important role in collective action, such as, management of common resources and collective marketing. Whilst literature exists on the role of social capital in the use and adoption of improved agricultural technology, such literature is fraught with issues of the measurement of social capital beyond membership of farmers in groups. We hypothesized that different types of social capital influence the adoption of soil management options differently. This study looked at the measurement of social capital, differentiating between the main types of social capital and employed factor analysis to aggregate indicators of social capital into bonding, bridging, and linking social capital. Using logit analysis, the role of these types of capitals on influencing use of different soil management options was analyzed. The study found that bonding, bridging, and linking social capital all influence the adoption and use of different soil management options differently, a trend that might be similar for other agricultural technologies as well. The study recommends more research investments in understanding the differentiated outcomes of these forms of social capital on use and adoption of technologies to further guide agricultural interventions.